Research on Time-Driven Activity-Based Management System of Public Hospitals - Qiwen Jiang; Xueyuan Zhu; Lianghua Chen; Ziyuan Zhao; Yilong Chen (Frontiers Media S.A., 2022)
ObjectiveTo provide references for effective implementing cost management for public hospitals through establishing time-driven activity-based management (TDABM) system. The TDABM system was established from hospital cost accounting, budget, control, and performance.ResultsThe established TDABM system could improve the precision of hospital cost accounting, improve medical staff's working efficiency, realize the whole process of cost management, and enhance the competitiveness of the hospital.ConclusionThe activity of implementing TDABM in public hospitals had practical significance.